Percutaneous coronary revascularisation: is it ever worth what it costs?. Issue 10 (21st September 2007) - Mark, Daniel B
Abstract : "How could percutaneous coronary intervention without the risks and morbidities of heart surgery not be of benefit to patients? Hard experience teaches that such attractive "pathophysiological" simplifications are unreliable guides to practice and paradoxically may lead to worse rather than better treatment decisions" See also article on page 93 1238 1238 and viewpoint on page 93 1188 1188